Investigation of anti-depression effects and potential mechanisms of the ethyl acetate extract of Cynomorium songaricum Rupr. through the integration of in vivo experiments, LC-MS/MS chemical analysis, and a systems biology approach - Zhang, Xinyu; Li, Lingling; Chen, Jianxin; Hu, Mengyuan; Zhang, Yali; Zhang, Xuya; Lu, Yi (Frontiers in Pharmacology, 2023)
Background: Cynomorium songaricum Rupr. has long been used as an anti-inflammatory, antidepressant, and anti-aging agent in traditional Chinese medicine in Asia. Its ethyl acetate extract (ECS) has been identified as the main antioxidant component with neuroprotective and estrogen-like effects. However, the potential of ECS in treating depression has not been explored yet.We identified the primary metabolites in ECS in this study using liquid chromatographyelectrospray tandem mass spectrometry (LC-MS/MS). Network analysis was used to find the potential targets and pathways associated with the anti-neuroinflammatory depression action of the ECS. In addition, we established a corticosterone (CORT)-induced depression mouse model to assess ECS's antidepressant effects by monitoring various behavioral changes (e.g., sucrose preference, forced swimming, tail suspension, and open field tests) and biochemical indices of the hippocampus, and validating the network analysis results. Significant pathways underwent verification through western blotting based on network analysis prediction.Results: Our study demonstrates that ECS possesses significant antidepressant activity. The LC-MS/MS analysis of ECS identified 30 main metabolites, including phloridzin, phlorizin, ursolic acid, and naringenin, as well as other flavonoids, terpenoids, and phenolic acids. These metabolites were found to be associated with 64 candidate target proteins related to neuroinflammatory depression from the database, and ten hub proteins were identified through filtration: CXCL8, ICAM1, NOS2, SELP, TNF, IL6, APP, ACHE, MAOA and ADA. Functional enrichment analyses of the candidate targets revealed their primary roles in regulating cytokine production, inflammatory response, cytokine activity, and tumor necrosis factor receptor binding. In vivo, ECS improved hippocampal neuroinflammation in the mouse model. Specifically, ECS reduced the expression of inflammatory factors in the hippocampus, inhibited M1 microglial cell polarization, and alleviated depression through the regulation of the NF-κB-NLRP3 inflammation pathway.Based on experimental and network analysis, this study revealed for the first time that ECS exerted antidepression effect via anti-neuroinflammation. Our research provides valuable information on the use of ECS as an alternative therapeutic approach for depression.